(untitled) (AL MUNAZHZHARAH, 2024)
Religious justice is one of the executors of judicial power for the people seeking justice who are Islamic in relation to certain matters as intended in the law Article 1 of Law Number 50 of 2009 concerning religious justice. In the application of the law of examination in religious courts, there are often cases that require other parties, such as evidence submitted by witnesses who are not muslims (non muslim witnesses). The presence of non muslim witnesses in the trial certainly led to a renewal of the law. As a result, the application of procedural law in force in religious courts today is still incompatible and even contrary to the concept of Islamic law. The purpose of the study to be achieved is to find out the urgency of witnesses in religious courts according to the perspective of Islamic law and procedural law of religious courts and to find out the position of non muslim witnesses in religious courts according to the perspective of Islamic law and procedural law of religious courts. This research uses library research with a normative approach (literature law research). The data obtained in this study is sourced from primary data and secondary data collected and processed by editing and organizing, then analyzed descriptively qualitatively through inference of valid data sources. So it is hoped that research results and conclusions can be found that are coherent with the context of the problem. The results of this study, stated that the urgency of the witness in question both according to Islamic law and the procedural law of religious courts has the same implication, namely that it lies in the truth of his testimony when expressing an event by fulfilling certain conditions and being seen as having a good understanding of the event he is assessing. The position of non muslim witnesses in religious courts both according to Islamic law and the procedural law of religious courts of non muslim witnesses is positioned as a means of proof that lies in their testimony. About the acceptance of non muslim witnesses according to Islamic law is when in an emergency and not related to the Islamic religious creed. Whereas in the procedural law of pera d ilan religion, the testimony of non muslim can be accepted as a means of proving the judge’s consideration which is strengthened through oaths.